The effect of training intervention based on the theory of planned behavior on oral and dental health behaviors in pregnant women - Fatemeh Mohammadkhah; Razieh Mardani Amirhajelu; Maryam Bakhtiar; Saina Alempour Salemi; Marzieh Kevenjan; Ali Khani Jeihooni (BMC, 2023)
Abstract Background Pregnancy is a transient physiological condition that causes adverse oral and dental consequences. The present study aimed to determine the effect of a training intervention based on the theory of planned behavior on oral and dental behaviors in pregnant women. Methods This quasi-experimental study was conducted on 140 pregnant women (70 in the intervention group and 70 in the control group) supported by comprehensive health centers on the outskirts of Shiraz, Iran, in 2019-2020. The sampling was performed in each center by a simple random method. The tool included a demographic characteristics questionnaire, a questionnaire based on the theory of planned behavior, a self-care behavior questionnaire, and checklists for recording DMFT(Decayed, Missing due to caries, and Filled Teeth(DMFT)) and dental plaque indices. The questionnaires were completed before and 3 months after the intervention by both groups. The intervention group received six 50-min training sessions. The data were analyzed using SPSS 22, the chi-squared test, independent t-test, paired t-test, and descriptive statistics (p < 0.05). Results The mean ages of the intervention and control groups were 32.28 ± 6.14 and 31.84 ± 6.71, respectively. The results showed that the average scores of all constructs of the theory of planned behavior, dental plaque indices (PI), and MDFT in the intervention group significantly changed after the intervention (p < 0.001). Conclusion According to the results, training based on the theory of planned behavior was effective on dental and oral health behaviors in pregnant women and improved the clinical results of their self-care behaviors. Therefore, training sessions will increase the knowledge of pregnant women, and providing timely consultations and examinations can be helpful and effective in developing oral and dental health behaviors in pregnant women.